ISSUES AND PARTICULARITIES OF PROVING ECONOMIC CRIMES IN CRIMINAL PROCEEDINGS - Litvinova, Iryna; Shchurikova, Anna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: to investigate the procedural and forensic problems of proof in criminal proceedings about crimes in the field of economy and to consider the trends in the development of scientific research devoted to the above-mentioned crimes. Research methods: the methodological basis is a set of general and special methods of scientific knowledge. Logico-semantic and analytical methods were used to highlight the state of scientific research on the problems of proof in criminal proceedings about crimes in the field of economics. The method of documentary analysis made it possible to determine the concepts, signs and classification of crimes in the economic sphere. System-structural and structural-functional methods were used to identify the circumstances to be proven in criminal proceedings about crimes in the economic sphere. The systematic method made it possible to determine the system of investigative (detective) and covert investigative (detective) actions as means of proof in criminal proceedings about crimes in the economic sphere. Results: it was established that what constitutes evidence in criminal proceedings about crimes in the field of economy, the subject of evidence in the field of economic crimes in criminal proceedings is emphasized, namely, that this is a theoretical category that covers the list of circumstances regulated by the Criminal Procedure Code of Ukraine mandatory proof. The peculiarities of the implementation of those measures to ensure criminal proceedings, which are most often used during the investigation of crimes in the economic sphere, are highlighted, in particular, temporary access to things and documents, seizure of property, and the procedure for carrying out a preliminary arrest, which can precede the seizure of property, is analyzed. Discussion: peculiarities of proof in the field of economic crimes in criminal proceedings; concepts, signs and classification of crimes in the field of economy, their impact on the process of proof in criminal proceedings; circumstances to be proven in criminal proceedings about crimes in the economic sphere and peculiarities of conducting investigative (search) actions in criminal proceedings about crimes in the economic sphere.